2011
DOI: 10.4317/medoral.16.e6
|View full text |Cite
|
Sign up to set email alerts
|

The neural histogenetic origin of the oral granular cell tumor: An immunohistochemical evidence

Abstract: Aims: Granular cell tumor (GCT) is a rare neoplasm that can appear in any site of the body, but most are located intraorally. Its histogenetic origin remains unclear. This report analyzes the immunoprofile of 15 cases of granular cell tumors, occurring in 13 women and 2 men and the lesions were located on the tongue or upper lip. Patient age ranged from 7 to 52. Methods: The patients demographic data and the cytological and architectural features of the lesions were analyzed in oral GCTs (n = 15). The lesions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(23 citation statements)
references
References 17 publications
0
18
0
3
Order By: Relevance
“…The immunoprofile of the GCT shows a strong and uniform positivity for S-100 protein (2,19). S-100 immunoreactivity (Fig.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…The immunoprofile of the GCT shows a strong and uniform positivity for S-100 protein (2,19). S-100 immunoreactivity (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…In a study with 42 oral GCT, all cases were found to be positive for S-100 (19). CD-68 is another traditionally used marker for identifications of GCT (2,19). Positive reactions for CD-68 can be found in cells of Schwannian lineage, but also in macrophage and occasionally in fibroblastic lineage (19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further this name was abolished due to S-100 and vimentin's positivity, as observed in the present case, favoring a neural origin of tumor cells. Other routine neural markers such p75 have also evidenced its nerve sheath differentiation [5]. On the other hand, the reason why these cells do not stain for S-100A6 protein, a form of S-100 protein found in other benign tumors of neural origin such schwannoma, neurofibroma, and palisaded encapsulated neuroma, needs to be clarified [6].…”
Section: Discussionmentioning
confidence: 99%